A Educação Moral e Religiosa Católica nas escolas do Estado: década de 70 - Ribeiro, José António de Queirós (Lusitania sacra, 2025)
In this article, we propose a panoramic analysis of the presence of the Catholic Church in State schools in the 1970s, taking as a starting point the conceptual, structural, legislative and pedagogical transformations that occurred then regarding teaching the subject of Catholic Religion and Morals, today called Catholic Religious and Moral Education. The aim, above all, of this analysis, is to highlight the response capacity of the Catholic Church, in its most diverse agents and protagonists in the processes invoked here, in responding to the multiple challenges then registered, framed and motivated by the environment of intra and extra renewal ecclesiastical that the Second Vatican Council and the 25th of April 1974 are inescapable references.